Lignin engineering through laccase modification: a promising field for energy plant improvement. Issue 1 (December 2015) - Wang, Jinhui; Feng, Juanjuan; Jia, Weitao; Chang, Sandra; Li, Shizhong; Li, Yinxin
Abstract Laccase (p -diphenol:dioxygen oxidoreductase, EC 1.10.3.2) is a member of the multicopper oxidases and catalyzes the one-electron oxidation of a wide range of substrates, coupled with the reduction of oxygen to water. It is widely distributed in bacteria, fungi, plants and insects. Laccases are encoded by multigene family, and have been characterized mostly from fungi till now, with abundant industrial applications in pulp and paper, textile, food industries, organic synthesis, bioremediation and nanobiotechnology, while limited researches have been performed in plants, and no application has been reported. Plant laccases share the common molecular architecture and reaction mechanism with fungal ones, despite of difference in redox potential and pH optima. Plant laccases are implicated in lignin biosynthesis since genetic evidence was derived from the ArabidopsisLAC4 andLAC17 . Manipulation of plant laccases has been considered as a promising and innovative strategy in plant biomass engineering for desirable lignin content and/or composition, since lignin is the major recalcitrant component to saccharification in biofuel production from lignocellulose, and therefore directly limits the fermentation yields. Moreover, plant laccases have been reported to be involved in wound healing, maintenance of cell wall structure and integrity, and plant responses to environmental stresses. Here, we summarize the properties and functions of plant laccase, and discuss the potential of biotechnological application, thus providing a new insight into plant laccase, an old enzyme with a promising beginning in lignocellulose biofuel production.